2019
DOI: 10.3906/vet-1803-63
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between egg weight, early embryonic development, and some hatching characteristics of Japanese quail (<i>Coturnix</i> <i>japonica</i>)

Abstract: The correlations between selected egg, embryo development, and chick traits were analyzed in three lines of Japanese quail subjected to intrafamily selection for 28th day body weight (group S) and in three lines of random control birds (group K). The significant correlation coefficients between egg weight and most of the traits observed after the first two days of incubation as well as chick weight and shank length were estimated. Most of the correlations obtained were significant in both groups. No statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…The increased chick yield could be partly attributed to difference in egg weight loss that there was a negative correlation between egg weight loss and day-old chick weight or chick yield (−0.26 and −0.21, respectively). These results were in agreement with that chick weight was primarily determined by initial egg weight and was secondarily determined by weight loss during incubation ( Marks, 1975 , Khurshid et al., 2004 , Grzegrzka and Gruszczynska, 2019 ). These results were also supported that decreased egg weight loss during incubation could increase chick weight ( Peebles et al., 1987 , Shahein and Khalifa, 2014 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The increased chick yield could be partly attributed to difference in egg weight loss that there was a negative correlation between egg weight loss and day-old chick weight or chick yield (−0.26 and −0.21, respectively). These results were in agreement with that chick weight was primarily determined by initial egg weight and was secondarily determined by weight loss during incubation ( Marks, 1975 , Khurshid et al., 2004 , Grzegrzka and Gruszczynska, 2019 ). These results were also supported that decreased egg weight loss during incubation could increase chick weight ( Peebles et al., 1987 , Shahein and Khalifa, 2014 ).…”
Section: Resultssupporting
confidence: 90%
“…The Pearson's correlation analysis results showed that the shank length was correlated to initial egg weight, day-old chick weight and chick yield without being affected by egg weight loss. The Pearson's correlations reported here for initial egg weight, day-old chick weight, and shank length (0.84, 0.24, and 0.34, respectively, Table 5 ) were lower than those reported previously (0.91, 0.57, and 0.58) ( Grzegrzka and Gruszczynska, 2019 ), but this is most likely because of the reduced sample size in this trial.…”
Section: Resultscontrasting
confidence: 82%
“…Regarding residual yolk sac weight, chicks from eggs stored for 3.5, 6.5, and 9.5 days, pre-heated or not, showed significantly lower results than the control group (p<0.05). The birth weight of Japanese quail is directly linked to egg weight (Grzegrzółka & Gruszczyńska 2019;Chimezie et al, 2020). Thus, the lower weight values of newly hatched chicks obtained in this study are attributed to the lower egg weight.…”
Section: A-bmentioning
confidence: 48%
“…The reduction in different reproduction traits, such as egg production, fertility, and hatchability due to selection for body weight which has a positive effect on egg weight increase (Anthony et al, 1996 andNestor et al, 2008). There were correlations between both embryo development and hatchability with hatching egg weight (Rocha et al, 2008 andGrzegrzółka andGruszczyńska, 2019). It is well known that genetic background of lines affected the differences of these traits (Brah et al, 2001).…”
Section: Introductionmentioning
confidence: 99%